Developmental stages of the Pekin duck (Anas platyrhynchos f. domestica) and the Mulard duck in artificial incubation - Magdalena Trela; Weronika Sołtysik; Kamil Kustra; Aleksandra Januszewska; Marcin W. Lis (Poultry Science)
Knowledge of the stages of avian embryo development is essential for the supervision of the incubation process in a hatchery.The hatching eggs of Pekin (Cherry Valley) and Mulard ducks (1800 eggs/breed) were incubated at a gradually decreased temperature (from 37.8 to 36.2°C) and RH 65-60 %. Embryological sampling (3 eggs/breed/collection) was on: 0-4, 5-12 and 3- 28/32 days of incubation (d.i) every 6, 12 h and 24 h, respectively. The incubation of the remaining eggs (2 × 1600 eggs) continued until the ducklings hatched. All discarded during candling and unhatched eggs were breakout analysed.The faster embryo development of Pekin duck in comparison to Mulard was already detected on 1 d.i. Two clear peaks of embryo mortality were observed. However, the 1st peak occurred for Pekin duck between 2 - 3 d.i. (HH 11-17), while for Mulard a critical peak in 4d.i. (HH 16-17). The 2nd peak was found for Pekin duck (17.7 % of all deaths) between 22 and 26 d.i., while for Mulard (57.3 % of all deaths) between 24 - 30 d.i. with the sharp mortality during the external pipping (29 d.i.).From the beginning of incubation, the subsequent stages of embryonic development of the Mulard are observed later than in the Peking duck. Moreover, both breeds of ducks are characterized by the different patterns of the timeline of embryo mortality. For this reason, the incubation program needs to be targeted individually for each with these breeds.